Flat rotation curves of z ∼ 1 star-forming galaxies. Issue 2 (4th February 2021) - Sharma, Gauri; Salucci, Paolo; Harrison, C M; van de Ven, Glenn; Lapi, Andrea
ABSTRACT: We investigate the shape of the rotation curves (RCs) of z ∼ 1 star-forming galaxies (SFGs) and compare them with local SFGs. For this purpose, we have used 344 galaxies from the K -band Multi-Object Spectrograph (KMOS) for Redshift One Spectroscopic Survey (KROSS). This sample covers the redshift range 0.57 ≤ z ≤ 1.04, the effective radii 0.69 ≤ Re  [kpc] ≤ 7.76, and the stellar masses 8.7 ≤ log ( M *  [M⊙ ]) ≤ 11.32. Using 3D BAROLO, we extract the H α kinematic maps and corresponding RCs. The main advantage of 3D BAROLO is that it incorporates the beam smearing in the 3D observational space, which provide us with the intrinsic rotation velocity even in the low spatial resolution data. We have corrected the RCs for pressure support, which seems to be a more dominant effect than beam smearing in high- z galaxies. Only a combination of the three techniques (3D-kinematic modelling + 3D-beam smearing correction + pressure gradient correction) yields the intrinsic RC of an individual galaxy. Further, we present the co-added and binned RCs constructed out of 256 high-quality objects. We do not see any change in the shape of RCs with respect to the local SFGs. Moreover, we notice a significant evolution in the stellar-disc length ( RD ) of the galaxies as a function of their circular velocity. Therefore, we conclude that the stellar disc of SFGs evolves over cosmic time (from z ∼ 1) while the total mass stays constant (within ∼20 kpc).